Early surgery for superficial supratentorial spontaneous intracerebral hemorrhage: a Finnish Intensive Care Consortium study - Luostarinen, Teemu; Satopää, Jarno; Skrifvars, Markus B.; Reinikainen, Matti; Bendel, Stepani; Curtze, Sami; Sibolt, Gerli; Martinez-Majander, Nicolas; Raj, Rahul (Acta Neurochirurgica, 2020)
The benefits of early surgery in cases of superficial supratentorial spontaneous intracerebral hemorrhage (ICH) are unclear. This study aimed to assess the association between early ICH surgery and outcome, as well as the cost-effectiveness of early ICH surgery.